Understanding Proteolytic Processing of Melanoma Cell Adhesion Molecule (MCAM) in Cutaneous Melanoma - George, Tenielle (Curtin University, 2023)
Melanoma is a type of skin cancer and is one of the most common cancers in Australia. Due to the aggressive nature of melanoma, an improved understanding of its progression is required. In this thesis, the processing of “Melanoma Cell Adhesion Molecule” (MCAM), a protein that contributes to melanoma metastasis, was explored in detail. In particular, we found that MCAM undergoes at least two cleavage events, generating protein fragments that likely contribute to melanoma spread.